Nudging Behavior Change of Older Adults - Boiko, Mariia; Cingl, Lubomír, 1984-; Miklánek, Tomáš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This bachelor’s thesis explores nudge theory in behavioral economics and its potential implication in the domain of cognitive health of older adults. The importance of cognitive health to economics and the concept of nudging are first analyzed and discussed from a theoretical point of view, and its specific application is then proposed. The practical part of the thesis presents a design of an experiment aimed at evaluation and comparison of different nudging strategies‘ effectiveness in encouraging elderly people to engage in a weekly complex activity for improving cognitive health. The discussion presents a cost breakdown, recommendations, and suggestions for future research in the area.
Vedoucí práce: Lubomír Cingl
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses